Studying liquid-phase heterogeneous catalysis using the atomic force microscope - Young, Matthew J. (Kansas State University, 2016)
Characterization of the interactions of hydrogen with catalytic metal surfaces and the mass transfer processes involved in heterogeneous catalysis are important for catalyst development. Although a range of technologies for studying catalytic surfaces exists, much of it relies on high-vacuum conditions that preclude in-situ research. In contrast, atomic force microscopy (AFM) provides an opportunity for direct observation of surfaces under or near actual reaction conditions. Tapping-mode AFM was explored here because it expands AFM beyond the usual topographic information toward speciation and other more subtle surface information. This work describes using phase-angle data from tapping-mode AFM to follow the interactions of hydrogen with palladium. Both gas-solid and liquid-solid interfaces were studied. Real-time AFM phase-angle data allowed for the observation of multiphase mass transfer to and from the surface of palladium at atmospheric pressure and room temperature without the need for complex sample preparation. The AFM observations were quantitatively benchmarked against and confirm mass transfer predictions based on bulk hydrogen diffusion estimates. Additionally, they support recent studies that demonstrate the existence of multiple hydrogen states during interactions with palladium surfaces.
Keywords: Atomic force microscopy; Catalysis; In-situ; Hydrogenation